2023
DOI: 10.1073/pnas.2303779120
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting neuron-specific functions of circadian genes using modified cell-specific CRISPR approaches

Abstract: Circadian behavioral rhythms in Drosophila melanogaster are regulated by about 75 pairs of brain neurons. They all express the core clock genes but have distinct functions and gene expression profiles. To understand the importance of these distinct molecular programs, neuron-specific gene manipulations are essential. Although RNAi based methods are standard to manipulate gene expression in a cell-specific manner, they are often ineffective, especially in assays involving smaller numbers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…The low PDF peptide in the sLN v s projections of cyc 01 mutants can be rescued by vri overexpression 39 . To determine if vri expression also affects sLN v s morphology we expressed a line with a CRISPR/Cas9-based gRNA targeting the vri gene 53 under the control of the Pdf -Gal4 driver. We found that in Pdf > Cas9 + vri-g flies neither the distance until branching point in the s-LN v s (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The low PDF peptide in the sLN v s projections of cyc 01 mutants can be rescued by vri overexpression 39 . To determine if vri expression also affects sLN v s morphology we expressed a line with a CRISPR/Cas9-based gRNA targeting the vri gene 53 under the control of the Pdf -Gal4 driver. We found that in Pdf > Cas9 + vri-g flies neither the distance until branching point in the s-LN v s (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the Pdf null mutant background, other genetic factors could contribute to the sexual dimorphism observed in behavioral rhythms. We therefore employed a tissue-specific CRISPR-Cas9 mediated knockout of Pdf in both males and females, as described in a recent study that focused on males [57]. To assess the efficiency of the manipulation we stained for PDF in flies that constitutively expressed Pdf gRNA and Cas9 in Pdf + neurons.…”
Section: Resultsmentioning
confidence: 99%
“…While a previous study conducted in males did not find a correlation between the misrouting induced by the loss of Pdf during development and the loss of behavioral rhythms in adults [60], it is possible that the sex differences in Pdf 01 and Pdf > Pdf -g; Cas9 flies were due to developmental effects. The AGES system was previously employed to rule of a developmental contribution to the Pdf mutagenesis phenotypes [57], but a recent study showed that AUXIN exposure short-and long-term changes in physiology and behavior [61]. Therefore, we employed a temperature-sensitive Gal80 variant with ubiquitous expression to conditionally inhibit Gal4-mediated expression of the Pdf guide and Cas9 [62].…”
Section: Resultsmentioning
confidence: 99%
“…To gain transgenic access to these neurons, we screened expression patterns of Janelia split-GAL4 driver lines from the Rubin Lab with the fluorescent protein expressed from UAS-EGFP . We looked for a driver line exhibiting the characteristic axonal bifurcation of the ITP + LNd and identified a novel split-GAL4 driver line, ss00639-GAL4 33 (Figure 2A): it only labels the two ITP + LNs. There is also the MB122B-GAL4 34 line, which labels the two ITP + LNs and two other circadian neurons, the Trissin + LNds (Figure S2D).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the morning sleep/activity effect of activation and inhibition shown above, we further pursued the contribution of dopamine and Dop1R1 to the two ITP + LNs. To this end, we employed a CRISPR/Cas9 mutagenesis method 26,33,41 to specifically knock out Dop1R1 function in wake-promoting ITP + LNs. Given that Dop1R1 is known as an excitatory dopamine receptor, 42 our hypothesis was that knocking out Dop1R1 in these neurons would diminish their activity, leading to reduced wake-promotion throughout the day.…”
Section: Resultsmentioning
confidence: 99%